2022
DOI: 10.1111/ajt.17125
|View full text |Cite
|
Sign up to set email alerts
|

Elevated cell-free DNA in respiratory viral infection and associated lung allograft dysfunction

Abstract: Respiratory viral infection (RVI) in lung transplant recipients (LTRs) is a risk for chronic lung allograft dysfunction (CLAD). We hypothesize that donor-derived cell-free DNA (%ddcfDNA), at the time of RVI predicts CLAD progression. We followed 39 LTRs with RVI enrolled in the Genomic Research Alliance for Transplantation for 1 year.Plasma %ddcfDNA was measured by shotgun sequencing, with high %ddcfDNA as ≥1% within 7 days of RVI. We examined %ddcfDNA, spirometry, and a composite (progression/failure) of CLAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…They then subsequently decrease over time, reaching a steady state 2–4 months following transplant 106–109 . Unfortunately whilst the sensitivity of using dd‐cfDNA to detect lung allograft injury is promising, it lacks specificity and cannot reliable distinguish between ACR, AMR and infection limiting its clinical utility at present 110,111 …”
Section: Outcomes Of Lung Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…They then subsequently decrease over time, reaching a steady state 2–4 months following transplant 106–109 . Unfortunately whilst the sensitivity of using dd‐cfDNA to detect lung allograft injury is promising, it lacks specificity and cannot reliable distinguish between ACR, AMR and infection limiting its clinical utility at present 110,111 …”
Section: Outcomes Of Lung Transplantationmentioning
confidence: 99%
“…[106][107][108][109] Unfortunately whilst the sensitivity of using dd-cfDNA to detect lung allograft injury is promising, it lacks specificity and cannot reliable distinguish between ACR, AMR and infection limiting its clinical utility at present. 110,111…”
Section: Histopathology: Molecular Diagnosticsmentioning
confidence: 99%
“…In addition, change in dd-cfDNA levels versus the absolute value (which is different for single versus bilateral transplant) has been shown to have better diagnostic accuracy for ALAD [39 & ]. One drawback is dd-cfDNA level alone does not delineate the type of allograft, in acute symptomatic infection from respiratory viruses, dd-cfDNA levels have been shown to be elevated similarly to ACR episodes [40], but such elevations are not seen in asymptomatic infections, suggesting a possible role in delineating colonization versus true clinical infection [37].…”
Section: Future Directionsmentioning
confidence: 99%
“…Other studies have also found an association between RVIs and graft dysfunction in LTxRs 1-2 y after infection. 116 Many respiratory viral pathogens are capable of invading human epithelial cells within the respiratory tract and elevating the levels of proinflammatory cytokines, some chemokines, and related signaling pathways. [117][118][119] Respiratory viruses like influenza, respiratory syncytial virus, and coronavirus variants can lead to hemorrhage and diffuse alveolar damage followed by fibrin deposition within the airways, preventing air exchange.…”
Section: Evs Induced By Rvis: Possible Role In the Development Of Cladmentioning
confidence: 99%
“…Other studies have also found an association between RVIs and graft dysfunction in LTxRs 1–2 y after infection. 116…”
Section: Evs Induced By Rvis: Possible Role In the Development Of Cladmentioning
confidence: 99%